Development of lineage- and subgroup-specific SNP markers for identification of Xanthomonas oryzae pv. Oryzae populations from the Philippine archipelago - Aung, Ei Ei; Atienza‐Grande, Genelou; Quibod, Ian Lorenzo; Nguyen, Marian Hanna; Cruz, Casiana Vera; Cumagun, Christian Joseph R.; Oliva, Ricardo (Wiley, 2025)
A specific and reliable diagnostic tool is required for the successful control of Xanthomonas oryzae pv. oryzae (Xoo), the causal agent of bacterial blight. The Xoo population in the Philippines has three major lineages (PX-A, PX-B and PX-C), and four subgroups in PX-A and PX-B have been classified based on single-nucleotide polymorphisms (SNPs) using whole genome alignment. This study aims to develop robust lineage- and subgroup-specific SNP markers using Xoo strains from different rice-growing regions of the Philippine archipelago. Primers were designed based on SNPs specific to Xoo lineages and subgroups. Two primer sets for each major lineage were specific to their targets. One primer set for PX-Aa4, five for PX-Ab9x and PX-Ac139, four for PX-Ad139, one for PX-Ba8, two for PX-Ba278 and PX-Bb23b and one for PX-Bc5 were also found to be very specific. Twenty-six isolates collected in 2014 from bacterial blight hotspot locations in Victoria, Laguna Province, the Philippines, were classified as lineage A and subgroup PX-Ab9x. Out of 87 isolates from 2015, 81 were classified as subgroup PX-Ab9x and six were lineage B but did not belong to any known subgroup. PCR-based allele-specific SNP markers can be recommended as a specific and reliable diagnostic tool for the identification of lineages and subgroups of Xoo populations in the Philippines using single colony and bacterial oozing-out detection methods in multiplex PCR. The information on the prevailing lineages and subgroups in the rice-growing areas in Laguna can be applied in breeding for bacterial blight resistance in particular geographical locations.